Influence of experience, training frequency, and sex on climbing-specific grip force in rock climbers of varying skill level - Nelson-Wong, E.; Lorbiecki, C.; Wood, S.; Huang, S.; Crawley, J.; Higgins, E.; Parker, L.; Cowell, K. (Journal of Applied Biomechanics, 2025)
Rock climbing is a growing sport at both professional and recreational levels. Rock climbing requires specific hand positions with high force outputs to adapt to changing terrain requirements. The purpose of this study was to explore associations between years of climbing experience, the frequency of training, and skill level on force production in 2 different climbing-specific hand positions. A secondary purpose was to investigate sex differences in force output across climbing skill levels. Forty-nine participants ranging from Beginner to Expert skill participated. Maximum isometric pull force was tested in half-crimp and open-hand positions. Force output was larger in half-crimp versus open-hand positions. Higher skill, years of experience, and training frequency were all significantly correlated to greater force output in both hand positions. There were no force differences between males and females for Beginner/Intermediate and Advanced levels; however, males had higher force than females for Expert groups. These findings provide insight for athletes, coaches, and clinicians working with climbers regarding tissue adaptations specific to climbing grip. These findings have implications for climbing-specific training, expectations for force output, injury prevention, and reliance on hand force versus climbing technique for females climbing at high levels.